Implementation of the library automation system in high schools in Surabaya City - Kristyanto, Dian; Shintawati, Yanuastrid (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: High school-level school libraries in the city of Surabaya have begun to develop services and facilities, one of which is by building a library automation system. Problems arise about the orientation of the development carried out whether it aims to build benefits or only to meet the needs of the library. Purpose: The purpose of this study is to describe the implementation of the library automation system development that has been carried out by senior high schools in the city of Surabaya Method: The method used in this research is a quantitative approach focusing on the type of descriptive quantitative. The study used a sample of 60 respondents taken from a specified population of 266 high school library managers. The sampling technique used snowball sampling, then data collection using a questionnaire distributed via google form over three weeks. Findings: all variables used gave positive results because the value of the mode generated from each variable showed an answer which could mean that the respondents agreed with the variables that supported the implementation of the high school library automation system in Surabaya. Conclusion: This study resulted in the finding that the library manager has carried out the implementation because of the benefits generated by the library automation system.